Prevalence of systemic inflammatory response syndrome (SIRS) in hospitalized children: a point prevalence study - Grope Ilze; Pavare Jana; Gardovska Dace (BMC, 2009)
Abstract Background In accordance with the 1st International pediatric sepsis consensus conference, where sepsis was defined as SIRS associated with suspected or proven infection, we have identified the need to assess the prevalence of SIRS and sepsis in children with abnormal temperatures hospitalized in The Children's Clinical University Hospital in Latvia. Methods A descriptive prospective point prevalence study (using two time periods, each 24 h, randomly chosen) was conducted on all children (n = 943) treated in the hospital. All children with abnormal temperatures - fever or hypothermia (n = 92) - were included in the study. Questionnaires evaluating age-specific SIRS criteria were completed. The prevalence of SIRS was detected with 95% CI. Results Out of a total of 943 patients treated in the hospital, 10% (n = 92) had abnormal temperatures. In all these cases the abnormal temperature was a fever; hypothermia was not established in any patient. Of the children with fever, 72% (n = 66) had SIRS. Of the SIRS patients, 8% (n = 5) developed sepsis, 5% (n = 3) severe sepsis and 2% (n = 1) septic shock. Seventy-six percent (n = 50) of the SIRS patients had fever in combination with respiratory rate >2 SD above normal for age; 50% (n = 33) had fever with abnormal leukocyte count; 15% (n = 10) had fever with tachycardia >2 SD above normal for age. Most of the SIRS patients (39%, n = 25) were aged 2-5 years. Twenty-one percent (n = 14) of the children with SIRS and 50% (n = 2) of those with severe sepsis and septic shock had an underlying disease. In no case was SIRS and sepsis recognized by doctors and the diagnoses were not recorded on the patients' cards. Conclusion Our results would indicate a high risk for sepsis development in children with SIRS. Early SIRS diagnosis and awareness of risk of developing sepsis could change the medical approach to the patient in everyday clinical practice, eventually leading to early, goal-directed therapy for sepsis.